Effects of core training on balance performance in older adults: a systematic review and meta-analysis - Zhong, Yuanji; Guo, Wenhao; Chen, Pengwei; Wang, Yongshun (Frontiers in Public Health, 2025)
BackgroundCore training (CT) has been increasingly recognized as a promising intervention for improving balance in older adults, a demographic particularly susceptible to falls and fall-related injuries. This systematic review and meta-analysis sought to evaluate the efficacy of CT on balance in older adults, providing substantial evidence to establish its role in fall prevention strategies.MethodsA comprehensive and systematic search of multiple databases, including PubMed, Cochrane Library, Web of Science, EBSCOhost, Embase and Google Scholar, was conducted to identify relevant studies. Eligible studies included single-group trials or randomized controlled trials that assessed the impact of CT on balance outcomes in healthy older adults (aged ≥60 years). It utilized the Cochrane Risk of Bias 2 (RoB 2) tool to assess the risk of bias across all included studies. Data were extracted from eleven studies and analyzed using Review Manager software version 5.4 and Stata 17.0, evaluating both dynamic and static balance parameters.ResultsThe findings revealed statistically significant improvements in both dynamic and static balance metrics, including Gait Test (GT) (SMD = 0.32; 95% CI = 0.02, 0.63; p < 0.05), Functional Reach Test (FRT) (SMD = 0.82; 95% CI = 0.50, 1.24; p < 0.00001), Timed Up and Go (TUG) test (SMD = −0.81; 95% CI = −1.62, 0.00; p = 0.05), and One-Leg Stance Test (OLST) (MD = 3.19; 95% CI = 1.74, 4.64; p < 0.001). Subgroup analyses further indicated that CT had the most significant effect on dynamic balance, particularly in FRT. Additionally, longer intervention durations (≥45 min) resulted in more pronounced benefits for dynamic balance compared to shorter sessions. CT demonstrated superior effects on GT compared to Pilates Training (PT).ConclusionCT is a highly effective intervention for enhancing balance in older adults, supporting its integration into fall prevention programs. However, given the heterogeneity across studies, further rigorously designed trials with standardized intervention protocols and outcome measures are necessary to confirm the long-term benefits and optimal parameters for balance enhancement.Systematic review registrationInplasy.com, INPLASY202412006.